Compensating wages under different exchange rate regimes - Mathias Hoffmann (University of Cologne, Centre for Financial Research (CFR), 2005)
This paper analyses the interconnectedness between developing countries' domestic wage levels and their exchange rate choices. The theoretical model illustrates that differences in domestic wage levels are related to countries' exchange rate regimes. In particular, the level of domestic wages increases with the rigidity of the exchange rate regime. The empirical model explores the determinants of the domestic wage level in a cross-section of 38 developing countries. In line with the theoretical model, the economies under review experience a rise in the domestic wage level with an increase in the rigidity of their exchange rate regime.
Keywords: F33; F41; 330; Exchange Rate Regimes; Factor Prices; Monetary Policy; Uncertainty